Development of independent dose verification plugin using Eclipse scripting API for brachytherapy. (9th October 2022) - Zhou, Dejun; Nakamura, Mitsuhiro; Sawada, Yohei; Ono, Tomohiro; Hirashima, Hideaki; Iramina, Hiraku; Adachi, Takanori; Fujimoto, Takahiro; Mizowaki, Takashi
Abstract: In this study, an independent dose verification plugin (DVP) using the Eclipse Scripting Application Programming Interface (ESAPI) for brachytherapy was developed. The DVP was based on the general 2D formalism reported in AAPM-TG43U1. The coordinate and orientation of each source position were extracted from the translation matrix acquired from the treatment planning system (TPS), and the distance between the source and verification point ( r ) was calculated. Moreover, the angles subtended by the center-tip and tip-tip of the hypothetical line source with respect to the verification point ( θ and β ) were calculated. With r, θ, β and the active length of the source acquired from the TPS, the geometry function was calculated. As the TPS calculated the radial dose function, g ( r ), and 2D anisotropy function, F ( r, θ ), by interpolating and extrapolating the corresponding table stored in the TPS, the DVP calculated g ( r ) and F ( r, θ ) independently from equations fitted with the Monte Carlo data. The relative deviation of the fitted g ( r ) and F ( r, θ ) for the GammaMed Plus HDR 192 Ir source was 0.5% and 0.9%, respectively. The acceptance range of the relative dose difference was set to ±1.03% based on the relative deviation between the fitted functions and Monte Carlo data, and the linear error propagation law. For 64 verification points from sixteen plans, the mean of absolute values of the relative dose difference was 0.19%. The standard deviation (SD) of the relative dose difference was 0.17%. The DVP maximizes efficiency and minimizes human error for the brachytherapy plan check.